2011
DOI: 10.1016/j.procbio.2011.01.037
|View full text |Cite
|
Sign up to set email alerts
|

Biochemical and structural characterization of a β-1,3–1,4-glucanase from Bacillus subtilis 168

Abstract: a b s t r a c t ␤-1,3-1,4-Glucanases (E.C. 3.2.1.73) hydrolyze linked ␤-d-glucans, such as lichenan and barley ␤-glucan. Recombinant ␤-1,3-1,4-glucanase from Bacillus subtilis expressed in Escherichia coli and purified by Ni-NTA chromatography exhibited optimum activity at 50 • C and pH 6.0. The catalytic half-life at 60 • C decreased from 90 to 5 min when the enzyme was incubated in the presence and absence of Ca 2+ respectively. The kinetic parameters of lichenan hydrolysis were 2695, 3.1 and 1220 for V max … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
40
0
3

Year Published

2012
2012
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(45 citation statements)
references
References 33 publications
2
40
0
3
Order By: Relevance
“…The presence of Val69 seems to be compatible with a higher stability of the calcium site. This fact might explain the higher stability of the UEB-S lichenase compared to lichenases to B. subtilis 168 lichenase, which retained less than 40% of its activity after 10 min incubation at 60 • C [23]. Similar results were observed by Welfle et al [27] who suggested that the geometry of the Ca 2+ binding site might explain the different extent of stabilization of three hybrid glucanases due to Ca 2+ binding.…”
Section: Homology Modelingsupporting
confidence: 71%
See 1 more Smart Citation
“…The presence of Val69 seems to be compatible with a higher stability of the calcium site. This fact might explain the higher stability of the UEB-S lichenase compared to lichenases to B. subtilis 168 lichenase, which retained less than 40% of its activity after 10 min incubation at 60 • C [23]. Similar results were observed by Welfle et al [27] who suggested that the geometry of the Ca 2+ binding site might explain the different extent of stabilization of three hybrid glucanases due to Ca 2+ binding.…”
Section: Homology Modelingsupporting
confidence: 71%
“…Many Bacillus sp. secrete ␤-1,3-1,4-glucanases but a majority of them exhibit optimal temperatures lower than 65 • C. For example, the optimal temperature for B. subtilis MA139 enzyme was 40 • C (Qiao et al [22]) and for B. subtilis 168 lichenase it was 50 • C (Furtado et al [23]). B. macerans ␤-1,3-1,4-glucanase is among the most thermostable ␤-1,3-1,4-glucanases, which shows an optimal temperature at 65 • C and has a half-life of 40 min at 65 • C [24].…”
Section: Effect Of Temperature On Enzyme Activitymentioning
confidence: 99%
“…Attractively, Bgl16C1 was stable at pH ranging from pH 3.0 to 7.0 and kept 30% activity after treatment at pH 11.0 for 1 h. Bgl16C1 had lower optimum temperature (55°C) than PsBgl16A and PtLic16A (both at 70°C), but its optimal temperature for activity was higher than that of recombinant LicA (45°C) from Orpinomyces sp. PC-2 [9] and b-1,3-1,4-glucanase (50°C) from Bacillus subtilis 168 [13]. Furthermore, Bgl16C1 still had approximately 50-80% activity at 30-40°C, and so would exhibit good catalytic activity in the gut of animals [38].…”
Section: Discussionmentioning
confidence: 99%
“…EG16, EG16‐2, XTH and MLGase amino acid sequences were aligned using muscle with default settings within aliview . Following manual curation in aliview to remove obvious fragment sequences, manual realignment was performed using tertiary structural information from the following characterized GH16s as a guide: Bacillus subtilis licheninase (PDB ID 3O5S) (Furtado et al ., ), Paenibacillus macerans licheninase (PDB ID 1U0A) (Gaiser et al ., ), Tropaeolum majus NXG1 (PDB ID 2UWA) (Baumann et al ., ) and Vitis vinifera EG16 (PDB ID 5SV8) (McGregor et al ., ) (see figure in Eklöf et al ., ). The N and C termini were trimmed such that the fasta alignment file used as input for phylogenetic analysis comprised only the core β‐jellyroll domain (Appendix S8).…”
Section: Methodsmentioning
confidence: 99%